2024
DOI: 10.3390/jcm13071985
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High-Intensity Interval Training on Neuroplasticity Markers in Post-Stroke Patients: Systematic Review

Gines Montero-Almagro,
Carlos Bernal-Utrera,
Noelia Geribaldi-Doldán
et al.

Abstract: Background: Exercise has shown beneficial effects on neuronal neuroplasticity; therefore, we want to analyze the influence of high-intensity interval training (HIIT) on neuroplasticity markers in post-stroke patients. Methods: A systematic review of RCTs including studies with stroke participants was conducted using the following databases (PubMed, LILACS, ProQuest, PEDro, Web of Science). Searches lasted till (20/11/2023). Studies that used a HIIT protocol as the main treatment or as a coadjutant treatment wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(294 reference statements)
0
0
0
Order By: Relevance
“…High-intensity interval training can increase lactate levels and improve cerebral vascular function through related signaling pathways, activating neuroplasticity ( Huang et al, 2021 ). A Systematic Review showed that high-intensity interval training increased plasma concentrations of neuroplasticity markers such as lactate, BDNF, and VEGF in the brains of stroke patients and promoted functional recovery ( Montero-Almagro et al, 2024 ). Another animal study showed that high-intensity intermittent training promoted hippocampal mitochondrial function and ameliorated neuronal synaptic dysfunction via the lactate receptor (GPR81)-ERK1/2 pathway, in which lactate plays a mediating role ( Shang et al, 2023 ).…”
Section: Molecular Mechanisms Of Exercise-induced Neuroplasticitymentioning
confidence: 99%
“…High-intensity interval training can increase lactate levels and improve cerebral vascular function through related signaling pathways, activating neuroplasticity ( Huang et al, 2021 ). A Systematic Review showed that high-intensity interval training increased plasma concentrations of neuroplasticity markers such as lactate, BDNF, and VEGF in the brains of stroke patients and promoted functional recovery ( Montero-Almagro et al, 2024 ). Another animal study showed that high-intensity intermittent training promoted hippocampal mitochondrial function and ameliorated neuronal synaptic dysfunction via the lactate receptor (GPR81)-ERK1/2 pathway, in which lactate plays a mediating role ( Shang et al, 2023 ).…”
Section: Molecular Mechanisms Of Exercise-induced Neuroplasticitymentioning
confidence: 99%